PENGARUH PENDIDIKAN KESEHATAN TENTANG VAKSIN HPV MELALUI MEDIA VIDIO TERHADAP PENCEGAHAN KANKER SERVIKS PADA WANITA USIA SUBUR DI DESA WORI MINAHASA UTARA - Cut Mutiya Bunsal (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2021)
Background The low utilization of cervical cancer prevention services in Indonesia is caused by individual barriers including lack of knowledge and awareness about risk factors and prevention of cervical cancer for WUS. The purpose of this study was to determine the effect of Health Education about the HPV Vaccine through video media on the prevention of Cervical Cancer in women of childbearing age in Wori Village. This research uses the method Quasi Experiment by design one group pre test -post test design. The sample of this research is 29 respondents by using sampling Purposive Sampling. Furthermore, the data that has been collected is then analyzed using the Wilcoxon statistical test. The research results from the Wilcoxon test results obtained a value of P = 0.000 (<0.05) then Ha accepted H0 rejected. The conclusion in this study is the influence of Health Education about the HPV Vaccine through video media about prevention of Cervical Cancer in aged women in Wori Village.